Aplicación de estrategias competitivas en la creación de empresas constructoras en Colombia (2023)
Based on an idea of ​​business creation, the life cycle is presented, which can be defined in six relevant aspects: birth, growth, maturity, decline, liquidation or rebirth. The birth cycle describes the legal constitution for which, throughout the research, the authors refer and consider capturing in a document the key steps when undertaking, also, highlighting the significance from the legal area which contributes legal advantages depending on the constitution, growth and development of these companies. In the same sense, researchers, based on their experience and documentary support, contribute great value to the understanding in a simple and relevant way, in the stage of growth and adulthood for the complex civil works contract model, its legal and technical implications. , which highly affects economic, legal and social life, and which probably arise from an improper interpretation and application of the rules that regulate these commercial activities; The analysis carried out on the life cycle of project management from its initiation, planning, execution and closure is essential.